Managing Heritage Sites While Accelerating Cultural Heritage Tourism in Antalya, Turkey - Uluca Tümer, Ege; Lombardo, Angela; Doganer, Sedef (Fabbrica della Conoscenza, 2013)
Antalya is characterized by historic sites and monuments of great importance dating from Hellenistic, Roman, Byzantine, Seljukian and Ottoman periods and is one of Turkey's most popular tourist destinations. Xanthos-Letoon, Antalya, is inscribed in the UNESCO World Heritage List since 1988 and the city has also seven nominated properties in the tentative list. In 1980, tourism was encouraged to constitute a new sector as an economic and political objective and now the number of tourists visiting Antalya has reached 10.7 million. Besides the positive effects of the tourism development, some other problems occurred, such as rapid population growth and the speedy consumption of the historical, natural, and cultural resources related to this rise. By the time tourism industry in the area has mostly focused on sea-sun-sand tourism. Historical, natural and cultural entities have almost been forgotten, and the heritage management has become an important issue to be considered seriously. Within this context, this paper focuses on how to put forward the real values of Antalya's identity and encourage heritage tourism as a sustainable alternative. This paper discusses the strategies to enhance and accelerate the heritage tourism in Antalya, to improve the interaction between historic heritage and tourists while managing heritage sites visited by tourist flow, and to re-interpret the identity of Antalya, Turkey, as a province of many notable urban/ archaeological world heritage sites.
Keywords: cultural heritage tourism; heritage site management; world heritage sites; Antalya; kültürel miras turizmi; miras alanı yönetimi; dünya mirası alanları